The Response Of Bioactive Compounds In Coriander Plant (Coriandrum Sativum L.) To Foliar Application Of Moringa Leaf And Barley Seed Extracts And Bio-Fertilization (International Journal of Environmental Sciences, 2025)
Modern guidelines focus on enhancing plant productivity and growth through the use of organic extracts and biofertilizers, which are considered natural reservoirs of various nutrients. These substances are effective and readily absorbed by plants. A field experiment was conducted during the autumn season of 2024–2025 to enhance the bioactive compounds in coriander (Coriandrum sativum L.) using organic extracts and microbial inoculants, thereby reducing the harmful impact of chemical fertilizers.The experiment was Implemented using a split-plot arrangement within a randomized complete block design (R.C.B.D) with two factors:Factor I: Microbial treatments(Control without addition, Mycorrhiza at 10 g·L⁻¹, Trichoderma at 10 g·L⁻¹, and Bacillus at 10 g·L⁻¹), represented as M1, M2, M3, and M4, respectively.Factor II: Foliar spray extracts(Control without addition, moringa leaf extract at 10 g·L⁻¹, and sprouted barley extract at 100 g·L⁻¹), denoted as E1, E2, and E3, respectively.Treatment means were compared using the Least Significant Difference (L.S.D) test at a 0.05 probability level.The results revealed significant differences among both the individual and combined treatments. The individual treatment M4 exhibited significant superiority in total chlorophyll content, dry matter percentage, nitrogen, phosphorus, total phenolic compounds, and flavonoids in coriander leaves, with the highest values recorded as follows:(62.36 SPAD, 15.83%, 3.292%, 0.2389%, 65.70 mg·kg⁻¹ dry weight, and 29.61 mg·kg⁻¹ dry weight), respectively.As for potassium content, treatment M3 showed the highest value of 2.649%.The foliar spray treatments also showed significant effects, where treatment E2 recorded the highest chlorophyll content in the leaves (59.56 SPAD). Treatment E3 resulted in the highest values for dry matter percentage, phosphorus, and phenolic content, reaching (14.58%, 0.2291%, and 65.16 mg·kg⁻¹ dry weight), respectively.Regarding the interaction between the two factors, the combined treatment M4E3 achieved significant superiority in total chlorophyll content, dry matter percentage, total phenolics, and flavonoids in coriander leaves, with maximum values of (65.77 SPAD, 16.74%, 73.83 mg·kg⁻¹ dry weight, and 31.14 mg·kg⁻¹ dry weight), respectively.Additionally, the treatment M4E2 recorded the highest nitrogen percentage (3.781%), while M4E3 resulted in the highest phosphorus content (0.2427%), and M3E1 showed the highest potassium percentage (2.723%).